Selective Transformation of Isoeugenol to Licarin A using HKUST-1 Catalyst - Dang, Do Van; Oanh, Nguyen Kim; Long, Dang Van; Son, Le Thanh (VNU Journal of Science: Natural Sciences and Technology; Vol 39 No 4DO - 10.25073/2588-1140/vnunst.5613, 2023)
The research delineated the utilization of Cu-MOF (HKUST-1) as a proficient heterogeneous catalyst for the selective transformation of isoeugenol to licarin A. The HKUST-1 was synthesized through a straightforward methodology and its structure was confirmed by various characterization employing a range of techniques, including X-ray diffraction (XRD), scanning electron microscopy (SEM) with Energy Dispersive X-ray analysis (EDX), and N 2 adsorption/desorption. The catalyst exhibited outstanding catalytic efficacy in the selective oxidation of isoeugenol, resulting in a 75% yield of licarin A under mild conditions in the presence of TBHP. Furthermore, the catalyst demonstrated stability, retaining its activity after being reused at least four times without deterioration.